Progression of cortical dysfunction in CSF1R‐related leukoencephalopathy detected using single‐photon emission computed tomography. Issue 5 (16th June 2021) - Sakaguchi, Hiroka; Hasegawa, Itsuki; Minatani, Shinobu; Miyazawa, Naotaka; Okamoto, Kosuke; Mino, Toshikazu; Takeda, Akitoshi; Hatsuta, Hiroyuki; Yoshizaki, Takahito; Abe, Takato; Kondo, Yasufumi; Yoshida, Kunihiro; et al.
Abstract: Background: Hereditary diffuse leukoencephalopathy with spheroids (HDLS) is a rare autosomal dominant disease progressively affecting cognitive and motor functions, most often caused by mutations in the colony‐stimulating factor 1 receptor gene ( CSF1R ). Aim: To elucidate the mechanism of disease progression, changes in white matter lesions and cortical cerebral blood flow (CBF) were evaluated in cases during various stages of the disease. Methods: All patients were diagnosed with HDLS by confirming mutations in CSF1R . Regional CBF was evaluated using single‐photon emission computed tomography and was analyzed semiquantitatively. Results: Three cases (2 males and 1 female, ages 51, 53, and 48 years on admission, disease duration from 1 to 8 years) were registered. All cases exhibited different CSF1R mutations and progressive frontal dysfunction. Scores of the Frontal Assessment Battery and time in the Trail Making Test worsened as the disease progressed, whereas the Mini‐Mental State Examination score remained relatively stable. MRI revealed progressive white matter lesions in the frontal lobe and atrophy of the anterior body of the corpus callosum. Regional CBF was low in the medial frontal cortex in the early case, and the area of hypoperfusion spread to the lateral frontal cortex and parietal cortex as the disease progressed. CBF was maintained in the basal ganglia, thalamus, and occipital lobes. Conclusions: Hypoperfusion was initially observed in the medial frontal lobe and spread to the lateral frontal lobe and parietal lobe with disease progression. Spreading of accumulated abnormal proteins induced by mutation in CSF1R may be involved as a molecular mechanism of disease progression.